Quantification of Cadmium (Cd), Lead (Pb) and Chromium (Cr) in Sediment of the Lower Nam Ngum - LABOUNMI , Bouasavanh; PHIPHATPHON , Soudavone; PHONGSAVATH , Sengthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study to the determination of quantification of heavy metals in sediment of the Lower Nam Ngeum River was investigated. The target heavy metals were Cadmium (Cd), Lead (Pb) and Chromium (Cr). The sediment samples were collected from Vientiane Province and Vientiane Capital. The sampling was conducted once a month for a period of 3 months in May, June, and July 2020. After drying the sediment was digested using mixed acid (HCl: HNO3), filtered through Whatman No. 42 filter paper, adjusted volume and analyzed by Atomic Absorption Spectrometer (AAS) for heavy metals analysis. The analysis of the sediment samples taken from 8 points of 2 provinces (Vientiane Province and Vientiane Capital) in the three months showed that the pH value was between 4.1-5.9, the EC value was between 34-144 µS/cm. The study found that the level of cadmium was 3.39-5.15 mg/kg, lead 9.28 mg - 32.85 mg/kg and chromium 1.50 - 29.56 mg/kg. According to the analysis. The amount of each heavy metal in the sediment at each point and in 3 months was not much different and within the range of soil standard defined in the national environmental standard (2017).